Selected anti-tumor vaccines merit a place in multimodal tumor therapies - Weiss, Eva M.; Wunderlich, Roland; Ebel, Nina; Rubner, Yvonne; Schlücker, Eberhard; Meyer-Pittroff, Roland; Ott, Oliver J.; Fietkau, Rainer; Gaipl, Udo S.; Frey, Benjamin (Frontiers in Oncology, 2012)
Multimodal approaches are nowadays successfully applied in cancer therapy. Primary locally acting therapies such as radiotherapy (RT) and surgery are combined with systemic administration of chemotherapeutics. Nevertheless, the therapy of cancer is still a big challenge in medicine. The treatments often fail to induce long lasting anti-tumor responses. Tumor recurrences and metastases result. Immunotherapies are therefore ideal adjuncts to standard tumor therapies since they aim to activate the patient`s immune system against malignant cells even outside the primary treatment areas (abscopal effects). Especially cancer vaccines may have the potential both to train the immune system against cancer cells and to generate an immunological memory, resulting in long-lasting anti-tumor effects. However, despite promising results in phase I and II studies, most of the concepts finally failed. There are some critical aspects in development and application of cancer vaccines that may decide on their efficiency. The time point and frequency of medication, usage of an adequate immune adjuvant, the vaccine’s immunogenic potential, and the tumor burden of the patient are crucial. Whole tumor cell vaccines have advantages compared to peptide-based ones since a variety of tumor antigens are present. The master requirements of cell-based, therapeutic tumor vaccines are the complete inactivation of the tumor cells and the increase of their immunogenicity. Since the latter is highly connected with the cell death modality, the inactivation procedure of the tumor cell material may significantly influence the vaccine’s efficiency. We therefore also introduce high hydrostatic pressure (HHP) as an innovative inactivation technology for tumor cell based vaccines and outline that HHP efficiently inactivates tumor cells by enhancing their immunogenicity. Finally studies are presented proving that anti-tumor immune responses can be triggered by combining RT with selected immune therapies.